Chondroitin Sulfate Capsule System for Efficient and Secure Gene Delivery - Tomoaki Kurosaki; Takashi Kitahara; Shintaro Fumoto; Koyo Nishida; Kayo Yamamoto; Hiroo Nakagawa; Yukinobu Kodama; Norihide Higuchi; Tadahiro Nakamura; Hitoshi Sasaki (Frontiers Media S.A., 2010)
Purpose. In this study, we developed various ternary complexes of encapsulated polyplexes and lipoplexes using chondroitin sulfate (CS) and investigated their universal usefulness for gene delivery. Methods. To prepare the cationic complexes, pDNA was mixed with some cationic vectors such as poly-L-arginine, poly-L-lysine, N-[1-(2, 3-dioleyloxy) propyl]-N, N, N-trimethylammonium chloride (DOTMA)-cholesterol liposomes, and DOTMA- dioleylphosphatidylethanolamine (DOPE) liposomes. CS was added to the cationic complexes for constructions of ternary complexes. We examined in vitro transfection efficiency, cytotoxicity, hematotoxicity, and in vivo transfection efficiency of the ternary complexes. Result. The cationic polymers and cationic liposomes bound to pDNA and formed stable cationic polyplexes and lipoplexes, respectively. Those cationic complexes showed high transgene efficiency in B16-F10 cells; however, they also had high cytotoxicity and strong agglutination with erythrocytes. CS could encapsulate the polyplexes and lipoplexes and form stable anionic particles without disrupting their structures. The ternary complexes encapsulated by CS showed high transgene efficiency in B16-F10 cells with low cytotoxicity and agglutination. As the result of animal experiments, the polyplexes had little transgene efficiency after intravenous administration in mice, whereas polyplexes encapsulated by CS showed specifically high transgene efficiency in the spleen. The capsulation of CS, however, reduced the high transgene efficiency of the lipoplexes. Conclusion. These results indicate that CS can contribute to polyplex-mediated gene delivery systems for effective and safe gene therapy.